2020
DOI: 10.18805/ijar.b-4205
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Egg Production and Egg Quality Attributes in Japanese Quails through Partial Periods

Abstract: Background: Egg production efficiency is typically measured through age and body weight at sexual maturity, egg number and egg weight during certain production periods. Increased egg weight and number of eggs are the primary purpose of the laying bird breeding programmes. Partial period analysis enhances selection process as the variations occurring throughout the bird’s productive life are identified and helps in the selection decisions. The current study aimed to study the genetic parameters such as heritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The egg quality parameters such as egg weight, shape index, specific gravity, albumen index, yolk index, Haugh unit score, yolk colour, shell thickness and shell percentage values presented in Table 6 were comparable with that of previous studies (Kumari et al (2016); Subhashini et al (2018 b); Monika et al (2020) in different strains of Japanese quails.…”
Section: Egg Quality Parameterssupporting
confidence: 86%
“…The egg quality parameters such as egg weight, shape index, specific gravity, albumen index, yolk index, Haugh unit score, yolk colour, shell thickness and shell percentage values presented in Table 6 were comparable with that of previous studies (Kumari et al (2016); Subhashini et al (2018 b); Monika et al (2020) in different strains of Japanese quails.…”
Section: Egg Quality Parameterssupporting
confidence: 86%
“…[17] showed that the genetic and phenotypic correlation between the characteristic of the number of eggs produced and the characteristic of egg weight was negatively correlated (-0.22, -0.18) in three chicken breeds (Penedesenca Negre, Prat Lleonada, Empordanesa Roja), and estimates of the heritability for the egg production were 0.20, 0.31, and 0.33 respectively. While in a study by the researcher [18] in which the Japanese quail was used, the phenotypic correlations for the characteristic of egg production between the productive periods were all positive and ranged between the three productive lines between (0.173 -0.614, 0.110 -0.465, 0.015 -0.371), respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Compared with pig egg extract and toad egg extract, chicken egg white extract is more convenient to obtain, the amount obtained is greater and the extraction process should be sterile (Monika 2021). This extract can be directly used for cell culture without filtration and sterilization and has greater application value (Lyayla 2021).…”
Section: Resultsmentioning
confidence: 99%